Seasonal influences on the levels of particulate metals In Kuantan River, East Coast Malaysia using principal component analysis - Faudzi, Fikriah; Yunus, Kamaruzzaman; Miskon, Mohd Fuad; Sabuti, Asnor Azrin; Azid, Azman (2018)
Principal component analysis (PCA) were performed to evaluate temporal variations of trace metals of Kuantan River waters. Water samples from 12 sampling stations were taken from downstream of the estuary towards the upstream of Kuantan River during the Northeast Monsoon (NEM) and Southwest Monsoon (SWM). Particulate metals were filtered, dried, weighed, analyzed using Teflon Bomb digestion processes and detected using ICP-MS. The metals distribution in suspended particulate matter was found influenced by monsoon seasons particularly during NEM. The PCA/FA identified six varifactors, which were responsible for 83.30% of total variance in the dataset. The PCA results showed that the main source of river water pollution is mostly due to the point sources such as domestic wastewater, wastewater treatment plants and industries as well as non-point sources namely agriculture and oil palm plantations. This study illustrates the usefulness of PCA for identification of pollution sources and understanding temporal variations in river water for effective river water management.